FACTORS INFLUENCING THE INNOVATION CAPABILITY IN SMALL-SCALE INDUSTRIAL ACTIVITIES IN WEST SUMATERA - Zednita Azriani; Rusda Khairati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
This study generally identifies the factors that influence the innovation carried out by food-based Small Industries in developing their business. In particular, this study aims to identify innovations that have been carried out by small industry players and the factors that influence innovation by small industries in West Sumatra. Descriptive qualitative and quantitative analysis were used. Quantitative analysis was done using the logit model. The results of the study showed that the number of small industrial entrepreneurs who innovate in the form of products, processes, technology, and packaging is still very low. Small industry entrepreneurs who innovated related to products were only 6.7%, while none of the small industry entrepreneurs did technological innovation. The most innovative innovation activity carried out by small-scale entrepreneurs was packaging innovation, 48.3%. Product innovation was influenced significantly by the age of the entrepreneur, business experience, and participation in the organization. Packaging innovation was influenced significantly by education, business experience, dummy training and turnover. Technological innovation was significantly influenced by business experience, turnover, training participation.